2004
DOI: 10.1081/jdi-200031721
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Status in Hemodialysis as a Function of Fluid Adherence

Abstract: Previous work has shown that dialysis improves cognitive functioning in hemodialysis patients, perhaps due to improvements in anemia among these patients. Such improvements in cognitive performance may lead to better levels of self-care and adherence with treatment. This study examined the relationship between fluid adherence and cognitive functioning in patients receiving hemodialysis. One hundred forty-seven patients were assessed with a brief screening instrument, the Cognistat, to determine their current l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…71 Cognitive impairment in ESRD 88 haemodynamic instability during the procedure, and solute shifts ( Figure 2). 89 Vitamin D deficiency in patients undergoing haemodialysis is associated with reduced cognitive function compared to cognitive function in vitamin D sufficient patients undergoing haemodialysis, particularly in domains assessing executive function; an associ ation of vitamin D with memory has not been shown. 84 FGF-23 is a phosphaturic hormone that is primarily expressed in bone, but is also found in high concentrations within the brain.…”
Section: Pathophysiology Of Cognitive Impairmentmentioning
confidence: 98%
See 1 more Smart Citation
“…71 Cognitive impairment in ESRD 88 haemodynamic instability during the procedure, and solute shifts ( Figure 2). 89 Vitamin D deficiency in patients undergoing haemodialysis is associated with reduced cognitive function compared to cognitive function in vitamin D sufficient patients undergoing haemodialysis, particularly in domains assessing executive function; an associ ation of vitamin D with memory has not been shown. 84 FGF-23 is a phosphaturic hormone that is primarily expressed in bone, but is also found in high concentrations within the brain.…”
Section: Pathophysiology Of Cognitive Impairmentmentioning
confidence: 98%
“…113 Acute defects in cognition Acute disturbances in cognition, such as delirium, can develop during a dialysis session in patients with poorly controlled blood pressure, or as a result of hypo perfusion (linked to the rapid fluid shifts that might occur during dialysis) and metabolic derangements, especially hyponatraemia. 89 Many studies have performed repeated meas ures of cognitive function at various times during the dialysis cycle to examine the acute effects of dialysis on cognition. [114][115][116][117][118][119] Data from such studies have, however, been inconsistent, showing both improvement and worsening of cognitive function after dialysis, probably due to a wide range of eligibility criteria, timing and type of cognitive measurements, and the use of acetate instead of bicarbonate in early studies.…”
Section: Dialysis Disequilibriummentioning
confidence: 99%
“…These skills are beyond those of some patients; our past research found that approximately one third of hemodialysis patients had difficulty performing simple calculations [25]. A major feature of DIMA is that it can compute real-time totals, allowing patients to see their intake relative to their dietary prescription for the day for six main categories – sodium, potassium, phosphorus, fluid, protein, and calories – without having to perform any calculations themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Although patients are taught about portion sizes, they must be able to adjust food intake behavior [24]. Even if patients can read labels, they must be able to convert between different units of measure (e.g., milliliters to ounces) or add amounts over the course of a given day, abilities not to be assumed in the target population [25]. Various strategies are suggested to assist patients in limiting fluid intake on a daily basis, such as measuring daily allotted fluids into a pitcher and only taking liquids from that pitcher, but this limits a patient’s drink choice and social activities [26].…”
Section: Introductionmentioning
confidence: 99%
“…Demakis, Mercury, and Sweet (2000) concluded in their review of the literature that, as compared with other measures, the NCSE appears more relevant for patients of various ages and with varied neurological conditions. Studies of the NCSE support its utility with neurosurgical (Schwamm et al, 1987), hemodialysis (Evans, Wagner, & Welch, 2004), liver disease (Whiteside, Padula, Jeffrey, & Zetterman, 1996), traumatic brain injury (Veltman, VanDongen, Jones, Buechler, & Blostein, 1993), acute motor stroke (Hinkle, 2002), stroke rehabilitation (Mysiw, Beegan, & Gatens, 1989), psychiatric (Mitrushina, Abara, & Blumenfeld, 1994), and geriatric rehabilitation (Ruchinskas, Repetz, & Singer, 2001) patients.…”
Section: Ncse Advantagesmentioning
confidence: 92%